Dust Explosibility and Severity of Bayan and Tanito Coal - Wan Zaiton, Wan Sulaiman; Mohd Fadzil, Mohd Idris; Rafiziana, Md. Kasmani; Jolius, Gimbun (Wiley-VCH GmbH, Weinheim, 2024)
The assessment of the explosibility and severity characteristics of Bayan coal and Tanito coal was investigated over various concentrations in a 20 L Siwek spherical explosion chamber. The coals tested in this study were also compared with other organic dusts such as palm-based soap noodle, tea powder, black rice, and rice flour, which were tested using the same explosion chamber and procedures. The severity and explosibility of the coals increase as their concentration increases. The Pmax of Bayan coal (10.15 bar) is higher than that of Tanito coal (7.35 bar). The Kst of Bayan coal (48.04 bar m s−1) is also higher than that of Tanito coal (16.83 bar m s−1). Among all the dusts studied using the same chamber and procedures, palm-based soap noodle has the highest Pmax at 16 bar, while tea powder has the lowest Pmax at 6.35 bar. The results show that the explosibility and severity of the coals increase as the concentrations increase, and the moisture content, coal ranking, and different types of organic dust have a significant influence on the severity characteristics of dust explosions.